Successful long‐term outcome after combined hematopoietic stem cell transplantation and small bowel transplantation: A case report and review of the literature. (31st August 2019) - Na, Sera; Saldana, Blachy Davila; Peredo‐Pinto, Helka; Gonzalez, Corina Elena; Kroemer, Alexander Helmut; Hawksworth, Jason; Matsumoto, Cal Satoshi; Yazigi, Nada; Kaufman, Stuart; Fishbein, Thomas Marlon; Khan, Khalid
Abstract: Combining HSCT with SOT is an unusual and challenging undertaking given the complexities of immune modulation, the need to balance comorbidities, and the cumulative potential for complications. Early life‐threatening complications include infections and related effects, graft rejection, and GVHD can be expected to be increased especially if the HSCT is indicated for high‐risk cases such as individuals with severe combined immune deficiency and SOT that includes an intestine graft. Herein, we report such a case. Our patient is unique as a long‐term survivor. We review the literature and the features of our case, especially the timing of transplants and human leukocyte antigen matching for HSCT that resulted in a successful outcome and discuss how this may be applied to others in the future.